Endoplasmic reticulum stress: implications for inflammatory bowel disease pathogenesis - Kaser, Arthur (Curr Opin Gastroenterol, 2010)
PURPOSE OF REVIEW: To provide an overview of the emerging role of cellular stress responses in inflammatory bowel disease (IBD). RECENT FINDINGS: The unfolded protein response (UPR) is a primitive cellular pathway that is engaged when responding to endoplasmic reticulum stress and regulates autophagy. Highly secretory cells such as Paneth cells and goblet cells in the intestines are particularly susceptible to endoplasmic reticulum stress and are exceedingly dependent upon a properly functioning UPR to maintain cellular viability and homeostasis. Primary genetic abnormalities within the components of the UPR (e.g. XBP1, ARG2, ORMDL3), genes that encode proteins reliant upon a robust secretory pathway (e.g. MUC2, HLAB27) and environmental factors that create disturbances in the UPR (e.g. microbial products and inflammatory cytokines) are important factors in the primary development and/or perpetuation of intestinal inflammation. SUMMARY: Endoplasmic reticulum stress is an important new pathway involved in the development of intestinal inflammation associated with IBD and likely other intestinal inflammatory disorders.